Antibiogram pattern among cultures of Listeria monocytogenes isolated from frozen burger patties in Malaysia - Wong, Woan Chwen; Pui, Chai Fung; Robin, Tunung; Anyi, Ubong; Mohd Sahroni, Noor Hidayah; Mohamad Ghazali, Farinazleen; Ahmad, Noorlis; Cheah, Yoke Kqueen; Radu, Son (Universiti Putra Malaysia Press, 2012)
orty-one isolates of Listeria monocytogenes, which were obtained from raw burger patties, were tested for their susceptibility against eleven antibiotics by using standard disc diffusion method. In particular, 31.7% of the isolates were found to be not resistant to any of the antibiotic tested while the rest showed resistance to at least one antibiotic. The result showed that resistance to tetracycline was the most common (46.3%), followed by erythromycin (36.6%), amikacin (31.7%), and sulfamethoxazole-trimethoprim (17.1%). All the isolates of Listeria monocytogenes were sensitive towards imipenem and gentamicin. The findings of the present study revealed the presence of multidrug-resistant Listeria monocytogenes isolates in the processed meat products and hence suggested the emergence of antibiotic resistance in bacterial strains in the food chain.